TRPC3 positively regulates reactive oxygen species driving maladaptive cardiac remodeling - Kitajima, Naoyuki (2016)
Reactive oxygen species (ROS) produced by NADPH oxidase 2 (Nox2) function as key mediators of mechanotransduction during both physiological adaptation to mechanical load and maladaptive remodeling of the heart. This is despite low levels of cardiac Nox2 expression. The mechanism underlying the transition from adaptation to maladaptation remains obscure, however. We demonstrate that transient receptor potential canonical 3 (TRPC3), a Ca 2+-permeable channel, acts as a positive regulator of ROS (PRROS) in cardiomyocytes, and specifically regulates pressure overload-induced maladaptive cardiac remodeling in mice. TRPC3 physically interacts with Nox2 at specific C-terminal sites, thereby protecting Nox2 from proteasome-dependent degradation and amplifying Ca 2+-dependent Nox2 activation through TRPC3-mediated background Ca 2+ entry. Nox2 also stabilizes TRPC3 proteins to enhance TRPC3 channel activity. Expression of TRPC3 C-terminal polypeptide abolished TRPC3-regulated ROS production by disrupting TRPC3-Nox2 interaction, without affecting TRPC3-mediated Ca 2+ influx. The novel TRPC3 function as a PRROS provides a mechanistic explanation for how diastolic Ca 2+ influx specifically encodes signals to induce ROS-mediated maladaptive remodeling and offers new therapeutic possibilities.